Multifunctional hyaluronate - nanoparticle hybrid systems for diagnostic, therapeutic and theranostic applications - Kim,H; Park,Y; Stevens,MM; Kwon,W; Hahn,SK (Journal of Controlled Release, 2019)
Diagnostic and therapeutic nanoparticles have been actively investigated for the last few decades as new platforms for biomedical applications. Despite their great versatility and potency, nanoparticles have generally required further modification with biocompatible materials such as biopolymers and synthetic polymers for in vivo administration to improve their biological functions, stability, and biocompatibility. Among a variety of natural and synthetic biomaterials, hyaluronate (HA) has been considered a promising biomolecule with which to construct nanohybrid systems, as it can enable long-term and efficient delivery of nanoparticles to target sites as well as physiological stabilization of nanoparticles by forming hydrophilic shells. In this review, we first describe various kinds of HA derivatives and their interactions with nanoparticles, and discuss how to design and develop optimal HA-nanoparticle hybrid systems for biomedical applications. Furthermore, we show several exemplary applications of HA-nanoparticle hybrid systems and provide our perspectives to their futuristic translational applications.